Raman, Judd–Ofelt, and photoluminescence analysis of Ho3+/Yb3+-doped borotellurite glasses for potential laser applications - Mazlan, M.; Tan, Winie; Sazali, E.S.; Zaid, M.H.M.; Hisam, R. (Elsevier, 2024)
In this study, glasses with the composition (79-x) B2O3-xTeO2-20Li2O-0.5Ho2O3-0.5Yb2O3 (x = 0–50 mol%) were synthesized using the melt-quenching method to explore the spectroscopic effect of TeO2 and B2O3 as mixed glass formers. Raman spectroscopy indicated that increasing TeO2 content leads to depolymerization, characterized by a reduction in the relative area of TeO4 units. Absorption spectra revealed nine peaks related to transitions from 5I8 ground state to various excited states of Ho3+ ions, and one peak for the transition from the 2F7/2 ground state of Yb3+ ions. A negative bonding parameter suggests that there is primarily ionic interaction among Ho3+ and its ligands. However, the increase of Ω2 suggests that Ho3+ ions have relatively higher covalence and strong ligand polarizability, except at x = 40 mol% due to the rivalry among TeO2 and B2O3. Decrease in Ω4 and Ω6 reflect reduced glass rigidity due to increased NBO content, weakening the glass structure. Luminescence spectra showed green (526 nm) and red (642 nm) emissions from Ho3+ transitions of 5F4 → 5I8 and 5F5 → 5I8. Intriguingly, a novel peak at 738 nm associated with the 5F4 → 5I7 transition in Ho3+ ions, linked to energy transfer from Yb3+ to Ho3+. The stimulated emission cross section for the green and red emission were (0.324 – 0.347) × 10−20 cm2 and (0.387 – 0.423) × 10−20 cm2 respectively. These glasses demonstrate potential for advanced laser, green display, and photonic technology applications. © 2024 Elsevier Ltd